Festive television in the socialist world: From media events to media holidays. Issue 1 (1st April 2017) - Huxtable, Simon; Mihelj, Sabina; Bardan, Alice; Szostak, Sylwia
This article focuses on the ways in which socialist television sought to create a sense of extraordinary temporality out of the ordinary through its coverage of historical commemorations, national days, and secular and religious festivities. To do so, it develops the concept of 'media holidays', which draws on Dayan and Katz's seminal notion of media events, and the work of other scholars of media ritual, to show the ways in which socialist television created extraordinary temporalities through scheduling. Drawing on schedule analysis and archival documents, the article compares the cases of television in East Germany, the Soviet Union and Yugoslavia. It examines a number of different kinds of media holiday on socialist television, and shows how different kinds of holidays and commemoration were marked with different kinds of programming in which entertainment played an important role.